2019
DOI: 10.1155/2019/6468348
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Necrotizing Mediastinitis after Dental Extraction

Abstract: Mediastinitis is a rare, progressive, and destructive infectious process due to cervical or odontogenic infections, which, if not diagnosed early, may lead to several complications, including airway involvement and even an imminent risk of death. Herein, we report an unusual case of a 37-year-old male with a bilateral submandibular hard swelling after the left third molar extraction. After surgical intervention with submandibular drainage and antibiotic therapy, the infection persisted without explanation, sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
0
Order By: Relevance
“…Las principales complicaciones reportadas son: sepsis, shock séptico, síndrome de disfunción múltiple de órganos y muerte. (81,82,83,84,85)…”
Section: Complicacionesunclassified
“…Las principales complicaciones reportadas son: sepsis, shock séptico, síndrome de disfunción múltiple de órganos y muerte. (81,82,83,84,85)…”
Section: Complicacionesunclassified
“…Based on a search of PubMed, 37 cases of PM after a dental procedure have been reported in the literature since 1973, but the real number of cases found worldwide seems to be greatly underestimated. Although treatment in most cases requires only several hours of observation and prophylactic administration of antibiotics [ 1 ], lack of knowledge about the complication after dental intervention may lead to pericarditis, sepsis, and multiple-organ failure [ 5 ]. In 2011, Romeo et al [ 6 ] reported a case in which a 25-year-old woman underwent a scheduled third-molar extraction.…”
Section: Introductionmentioning
confidence: 99%